2021
DOI: 10.1007/s10433-021-00665-z
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of neuroticism in older adults predict lower executive functioning across time: the mediating role of perceived stress

Abstract: Neuroticism has been associated with individual differences across multiple cognitive functions. Yet, the literature on its specific association with executive functions (EF) in older adults is scarce, especially using longitudinal designs. To disentangle the specific influence of neuroticism on EF and on coarse cognitive functioning in old adulthood, respectively, we examined the relationship between neuroticism, the Trail Making Test (TMT) and the Mini-Mental State Examination (MMSE) in a 6-year longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 115 publications
(164 reference statements)
0
8
0
Order By: Relevance
“…Our models were hypotheses-driven (as stated in the Introduction) and the conceptual split of the selected domains (e.g., cognitive—executive functions) is grounded on relevant evidence 1 3 , 17 23 . Moreover, the inclusion of global scores for cognitive state, executive functions, and social cognition is a common practice in path analysis models 85 87 . Nonetheless, exploratory results including ACE-III subdomains instead of the total score in the models were consistent with our main interpretations (Supplementary material 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our models were hypotheses-driven (as stated in the Introduction) and the conceptual split of the selected domains (e.g., cognitive—executive functions) is grounded on relevant evidence 1 3 , 17 23 . Moreover, the inclusion of global scores for cognitive state, executive functions, and social cognition is a common practice in path analysis models 85 87 . Nonetheless, exploratory results including ACE-III subdomains instead of the total score in the models were consistent with our main interpretations (Supplementary material 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while vascular factors play an important role, the tendency to experience negative emotions might have other mechanisms or a direct role in WMH and cognitive function. For example, there is evidence that perceived stress (Da Silva Coelho et al, 2022;Montoliu et al, 2022) and physical fitness (Stephan et al, 2023a) are other promising pathways linking personality traits to brain health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous research showed a link between neuroticism and performance in cognitive tests: Older adults high in neuroticism perceived more stress which led to lower performance in executive function tasks across a study period of six years 15 . Further research showed that in older adults, neuroticism was associated with worse performance in working memory, executive function 16 and other cognitive performance tasks 17 .…”
Section: Introductionmentioning
confidence: 89%
“…Further research showed that in older adults, neuroticism was associated with worse performance in working memory, executive function 16 and other cognitive performance tasks 17 . Thus, neuroticism may be a candidate mediator of the negative effect of adversity on cognitive performance because of the known association between neuroticism and adversity 14 on one hand and the known association between neuroticism and cognition on the other hand 15 17 .…”
Section: Introductionmentioning
confidence: 99%